Combining Korean Traditional Patterns and Batik Cirebon Banji Pattern in Daily Hanbok - Myung-Gong Park; Hafiz Aziz Ahmad; Kahfiati Kahdar (ITB Journal Publisher, LPPM ITB, 2019)
The interest towards Korean culture has risen through the popularity of K-wave and thus artefacts related to Korea are gaining more interest as well. Hanbok, the Korean traditional costume is also increasingly popular, with people renting and wearing hanbok while visiting Korean traditional places. The popularity of hanbok led to the creation of daily hanbok, a modern interpretation of the traditional hanbok, which is easier and more comfortable to wear for the young generation while still retaining the beauty of the original costume. Cirebon, a coastal region in Indonesia, has a rich local cultural tradition influenced by Chinese culture. One of these influences can be observed in Cirebon's batik, which uses Chinese influenced motifs, such as Cirebon's banji pattern. Because there are similarities between Chinese and Korean culture, several Korean motifs are also found in banji patterns, such as the swastika, known as wan in China and man in Korea. This study tried to combine the traditional patterns from Korea and Cirebon's banji pattern and implemented the result in a daily hanbok that can be worn by young people from Indonesia and Korea as a symbol of the close and harmonious relations between Indonesia and Korea.